An AGT-based protein-tag system for the labelling and surface immobilization of enzymes on E. coli outer membrane. (1st January 2019) - Merlo, Rosa; Del Prete, Sonia; Valenti, Anna; Mattossovich, Rosanna; Carginale, Vincenzo; Supuran, Claudiu T.; Capasso, Clemente; Perugino, Giuseppe
Abstract: The use of natural systems, such as outer membrane protein A (OmpA), phosphoporin E (PhoE), ice nucleation protein (INP), etc., has been proved very useful for the surface exposure of proteins on the outer membrane of Gram-negative bacteria. These strategies have the clear advantage of unifying in a one-step the production, the purification and the in vivo immobilisation of proteins/biocatalysts onto a specific biological support. Here, we introduce the novel Anchoring-and-Self-Labelling-protein-tag (ASL tag ), which allows the in vivo immobilisation of enzymes on E. coli surface and the labelling of the neosynthesised proteins with the engineered alkylguanine-DNA-alkyl-transferase (H 5 ) from Sulfolobus solfataricus . Our results demonstrated that this tag enhanced the overexpression of thermostable enzymes, such as the carbonic anhydrase ( Ss pCA) from Sulfurihydrogenibium yellowstonense and the β -glycoside hydrolase ( Ss βGly) from S. solfataricus, without affecting their folding and catalytic activity, proposing a new tool for the improvement in the utilisation of biocatalysts of biotechnological interest.